The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.5195/emaj.2019.172
|View full text |Cite
|
Sign up to set email alerts
|

Volatility Model Choice for Sub-Saharan Frontier Equity Markets - A Markov Regime Switching Bayesian Approach

Abstract: We adopt a granular approach to estimating the risk of equity returns in sub-Saharan African frontier equity markets under the assumption that, returns are influenced by developments in the underlying economy. Four countries were studied -Botswana, Ghana, Kenya and Nigeria. We found heterogeneity in the evolution of volatility across these markets and also that two-regime switching volatility models describe better the heteroscedastic returns generating processes in these markets using the deviance information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
(48 reference statements)
0
2
1
Order By: Relevance
“…The MS(3)-AR(2) provides the empirical results of Nigeria's stock returns in three distinct phases; accumulation/distribution, big-move and excess/panic regimes. This finding is unique as compared to related studies such as Aliyu and Wambai (2018), Korkpoe and Howard (2019) and Yahaya and Adeoye (2020) whose studies provided evidence of Nigeria's stock market in two eras (appreciation and depreciation). Also, evidence from the three-regimes [MS(3)-AR(2)] estimation, established a high probability that the returns' system remains in the same state, it implied that only unconventional or severe events can switch the series from regime 1(accumulation/distribution phase) Markov Regime-Switching Autoregressive Model of Stock Market Returns in Nigeria Adejumo et al…”
Section: Conclusion and Policy Recommendationscontrasting
confidence: 43%
“…The MS(3)-AR(2) provides the empirical results of Nigeria's stock returns in three distinct phases; accumulation/distribution, big-move and excess/panic regimes. This finding is unique as compared to related studies such as Aliyu and Wambai (2018), Korkpoe and Howard (2019) and Yahaya and Adeoye (2020) whose studies provided evidence of Nigeria's stock market in two eras (appreciation and depreciation). Also, evidence from the three-regimes [MS(3)-AR(2)] estimation, established a high probability that the returns' system remains in the same state, it implied that only unconventional or severe events can switch the series from regime 1(accumulation/distribution phase) Markov Regime-Switching Autoregressive Model of Stock Market Returns in Nigeria Adejumo et al…”
Section: Conclusion and Policy Recommendationscontrasting
confidence: 43%
“…Hu and Shin (2008) applied MS-GARCH modeling by using weekly stock market index data of developing countries in East Asia. Marcucci (2005), Wang and Theobald (2008), Visković, Arnerić and Rozga (2014), Abounoori, Elmi and Nademi (2016), Lolea and Vilcu (2018) and Korkpoe and Howard (2019) applied MS-GARCH models on various stock market indexes. Ardia, Bluteau and Rüede (2019) found that the volatility structure of the bitcoin market shows regime changes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This model has become very prevalent, particularly in applied research. The regime-switching model has gained the attention of many scholars like Calvet and Fisher (2004), Masoud et al (2012), Beckmann and Czudaj (2013), Lux et al (2014), Nguyen and Walid (2014), Aliyu and Wambai (2018), Korkpoe and Howard (2019), Yahaya and Adeoye (2020) to mention but few. They have documented the distinctiveness and forecasting capabilities of Markov regime-switching against the commonly used GARCH models.…”
Section: Introductionmentioning
confidence: 99%